PENGHINDARAN PAJAK: THIN CAPITALIZATION DAN ASSET MIX - Memed Sueb (Universitas Pakuan, 2020)
The purpose of this study was to examine the effect of thin capitalization and asset mix consisting of capital intensity and inventory intensity on tax avoidance. The moderating variable used in this study is the Indonesian Sharia Stock Index (ISSI). The sample of this study consisted of 60 companies in the manufacturing sector at ISSI 2014 - 2017 which were selected by purposive sampling method. The analytical method used in this research is Moderated Regression Analysis (MRA). The results of this study indicate that thin capitalization, capital intensity, and inventory intensity have an effect on tax avoidance. ISSI is able to influence the relationship between thin capitalization, capital intensity, and inventory intensity and tax avoidance. The implication of the results of this study is that the government should have an anticipatory General Anti Avoidance Rule (GAAR) to prevent taxpayers from conducting transaction schemes for the purpose of tax avoidance.